2015
DOI: 10.3892/or.2015.3726
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylene iodonium interferes with cell cycle progression and induces apoptosis by modulating NAD(P)H oxidase/ROS/cell cycle regulatory pathways in Burkitt’s lymphoma cells

Abstract: Infection with Epstein-Barr virus (EBV) and its encoded latent membrane protein 1 (LMP1) play oncogenic roles in Burkitt's lymphoma (BL). Flow cytometry was used to measure cellular reactive oxygen species (ROS) concentrations, and cellular lactate generation and diphenylene iodonium (DPI) cytotoxicity were determined by analyzing lactate concentrations and cell viability. We also measured NAD(P)H oxidase (NOX) activity. Reverse transcriptase PCR and qPCR assays were used to analyze LMP1 levels, and protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The NOX family has been suggested as potential therapeutic targets in prostate and pancreatic cancers, as well as Burkitt's lymphoma, melanomas, glioblastomas and TKI-sensitive CML [ 33 36 , 49 52 ]. Of the seven NOX complex family members, NOX1, NOX2, NOX4, NOX5, and DUOX2 have all been identified as isoforms present in CML [ 27 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NOX family has been suggested as potential therapeutic targets in prostate and pancreatic cancers, as well as Burkitt's lymphoma, melanomas, glioblastomas and TKI-sensitive CML [ 33 36 , 49 52 ]. Of the seven NOX complex family members, NOX1, NOX2, NOX4, NOX5, and DUOX2 have all been identified as isoforms present in CML [ 27 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the mitotic CDK14/cyclin Y complex promotes Wnt signaling (26). Moreover, Cdc25 is known to be involved cell cycle regulation (27). Caspase recruitment domain 6 (CARD6), a microtubule-interacting protein, belongs to the CARD family (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies including our reports have shown that EBV-infected cells have high ROS levels that are modulated by various mechanisms [28], [29]. However, it is still not known whether Nrf2 is activated in EBV-infected cells and how Nrf2 activation is related to expression of EBV-related proteins.…”
Section: Introductionmentioning
confidence: 94%